EVALUATION OF ENZYME ACTIVITY OF CANDIDATE ISOLATES OF CELLULOLYTIC PROBIOTIC BACTERIA FROM THE LARGE INTENSTINE OF BALI PIG - K.A.B., Adnyana; Mudita, I M.; Cakra, I G.L.O. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This research aims to determine the enzyme activity of candidate isolates of cellulolytic probiotic bacteria from the large intestine of Bali pigs on various specific substrates which have been carried out at the Animal Feed and Nutrition Laboratory, Faculty of Animal Husbandry, Udayana University for 4 months. The study was carried out in a completely randomized design (CRD) with 5 treatments based on cellulolytic probiotic bacteria isolates obtained namely bacterial isolates with codes B2, C12, A5, A11 and C11. Observation of enzyme activity was carried out at several incubation period (30 minutes, 1 hour, 24 hours) and each was 4 replicated. The variables observed in this study were the activity of endo-glucanase (on CMC substrate), exo-glucanase (on avicel substrate), xylanase (on xylan substrate) and amylase (on starch substrate). The results showed that the five candidate isolates of cellulolytic probiotic bacteria isolated from the large intestine of bali pigs produced enzyme activities of 0.0005 – 0.0426 U; 0.00145 – 0.06598 U; 0.3686 – 17.353 U; 0.00136 – 0.05098 U respectively for the activity of endo-glucanase, exoglucanase, xylanase and amylase enzymes. Bacterial isolates with code C12 had higher activity of endo-glucanase, exo-glucanase and amylase than other isolates, while isolates with code C11 produced higher activity of xylanase enzymes than other isolates. Based on the results of the study, it can be concluded that the five candidate isolates of cellulolytic probiotic bacteria produced various enzyme activities, where the bacterial isolates with codes C11 and C12 each were bacterial isolates with higher enzyme activity compared to the other isolates.